Nicotine-induced impairments of spatial cognition and long-term potentiation in adolescent male rats. (February 2014) - Han, G; An, L; Yang, B; Si, L; Zhang, T
The aim of the present study was to investigate whether cognitive behavioral impairment, induced by nicotine in offspring rats, was associated with the alteration of hippocampal short-term potentiation (STP) and long-term potentiation (LTP) and to discuss the potential underlying mechanism. Young adult offspring rats were randomly divided into three groups. The groups include: control group (CC), nicotine group 1 (NC), in which their mothers received nicotine from gestational day 3 (GD3) to GD18, and nicotine group 2 (CN), in which young adult offspring rats received nicotine from postnatal day 42 (PD42) to PD56. Morris water maze (MWM) test was performed and then field excitatory postsynaptic potentials elicited by the stimulation of perforant pathway were recorded in the hippocampal dentate gyrus region. The results of the MWM test showed that learning and memory were impaired by either prenatal or postnatal nicotine exposure. In addition, it was found that there was no statistical difference of the MWM data between both nicotine treatments. In the electrophysiological test, LTP and STP were significantly inhibited in both NC and CN groups in comparison with the CC group. Notably, STP in CN group was also lower than that in the NC group. These findings suggested that both prenatal and postnatal exposure to nicotine induced learning and memory deficits, while the potential mechanism might be different from each other due to their dissimilar impairments of synaptic plasticity.